Information Literacy and Entrepreneurial Behavior of Culinary Business Actors in Makassar City: Determinants of Small Business Performance - Ilma Wulansari Hasdiansa; Sitti Hasbiah (Pinisi Journal of Entrepreneurship Review, 2023)
This study aims to analyze the determinants that affect the performance of small businesses in the culinary sector in Makassar City, with a focus on information literacy and entrepreneurial behavior. This study examines information literacy and entrepreneurial behavior both partially and simultaneously on small business performance. This research is a quantitative study with a population of 289 culinary businesses registered at the Makassar City Cooperative and SME Office. Data obtained through the distribution of questionnaires with a Likert scale. The analysis technique used is descriptive statistical analysis and inferential statistical analysis in the form of normality, linearity, hypothesis testing, partial significance test, simultaneous significance test, and coefficient of determination test. The results showed that partially and simultaneously the variables of information literacy and entrepreneurial behavior had a positive and significant effect on small business performance in culinary businesses in Makassar city. The results of the study clearly show that information literacy and entrepreneurial behavior are determinant factors of small business performance of culinary business actors in Makassar city.